Mechanism of allosteric activation of TMEM16A/ANO1 channels by a commonly used chloride channel blocker - Ta, C; Adomaviciene, A; Rorsman, N; Garnett, H; Tammaro, P (Wiley, 2016)
Calcium-activated chloride channels (CaCCs) play varied physiological roles and constitute potential therapeutic targets for conditions such as asthma and hypertension. TMEM16A encodes a CaCC. CaCC pharmacology is restricted to compounds with relatively low potency and poorly defined selectivity. Anthracene-9-carboxylic acid (A9C), an inhibitor of various chloride channel types, exhibits complex effects on native CaCCs and cloned TMEM16A channels providing both activation and inhibition. The mechanisms underlying these effects are not fully defined.Patch-clamp electrophysiology in conjunction with concentration jump experiments was employed to define the mode of interaction of A9C with TMEM16A channels.In the presence of high intracellular Ca(2+) , A9C inhibited TMEM16A currents in a voltage-dependent manner by entering the channel from the outside. A9C activation, revealed in the presence of submaximal intracellular Ca(2+) concentrations, was also voltage-dependent. The electric distance of A9C inhibiting and activating binding site was ~0.6 in each case. Inhibition occurred according to an open-channel block mechanism. Activation was due to a dramatic leftward shift in the steady-state activation curve and slowed deactivation kinetics. Extracellular A9C competed with extracellular Cl(-) , suggesting that A9C binds deep in the channel's pore to exert both inhibiting and activating effects.A9C is an open TMEM16A channel blocker and gating modifier. These effects require A9C to bind to a region within the pore that is accessible from the extracellular side of the membrane. These data will aid the future drug design of compounds that selectively activate or inhibit TMEM16A channels.